Comparative Analysis of Sustainable Mobility in Mexico City and Santiago de Chile - Robles-Andrade, Elias (2023)
Sustainable mobility is one of the pending issues in the metropolises that aspire to develop in a scenario typical of smart cities, within the framework of the 2030 Agenda and the Objectives for Sustainable Development. In this research, the mobility in Mexico City and Santiago de Chile is addressed, through a comparative analysis of public policies and national and local regulatory instruments that regulate the general aspects of the goals or objectives for mitigating climate change and transitioning into a sustainable mobility scheme. With a qualitative approach and an exploratory and descriptive scope, the research aims to show the dissimilarities, convergences, and opportunities of the two cities to reach this transition. In a context in which the Global Emissions Gap Report shows that Mexico is not even on the path to meeting its own goals in this area and that the countries of Latin America, in general, are not making sufficient efforts to mitigate emissions in highly strategic sectors, both Mexico and Chile are characterized by promoting, signing, and ratifying international treaties on the reduction of GHG emissions, incorporating these agreements into their regulatory framework and planning schemes. However, at the execution level, there is an evident lack of fully effective instruments.